Penyusunan Modul Elektronik Berbasis Pendekatan Saintifik Pada Materi Momentum dan Impuls untuk SMA Kelas X - Fadiah Azmi Rahmasari; Pujayanto Pujayanto; Elvin Yusliana Ekawati (Universitas Sebelas Maret, 2022)
The purpose of this study was to produce and determine the feasibility of a scientific-based physics electronic module on Momentum and Impulse material for SMA Class X which was developed. This research is a development research (R&D) using the ADDIE development model. The steps used in this research are analysis, design, and development (ADD). The types of data used are quantitative and qualitative. Data was collected using interview and questionnaire techniques. The instrument used to collect data has been validated by the supervisor. The research data were obtained from two expert validators, two reviewers, three colleagues, and 10 students of SMA Al-Islam 1 Surakarta as an initial trial. The quantitative data analysis technique uses five classification criteria by Saifudin Azwar and the qualitative data uses the Miles and Huberman model. The results showed that: 1) the scientific-based physics electronics module on momentum and impulse material for SMA Class X was successfully made with product specifications (.apk) that could be applied to Android, the use of a light smartphone memory of 13 megabytes (MB), can be used online or offline so as to save internet data consumption, the module is easy to operate for everyone, and the module can support distance learning because the language is easy to understand and has clear instructions (user friendly). 2) The results of the validation and feasibility of the electronic module were declared to have very good criteria by the validator with a percentage of 100% in all aspects and according to student responses in the initial trial the module had very good criteria in all aspects of 80%-.